Rising rural body-mass index is the main driver of the global obesity epidemic in adults. - Bixby, Honor (2019)
NCD Risk Factor Collaboration (NCD-RisC)* Abarca-Gomez, Leandra Abdeen, Ziad A Abdrakhmanova, Shynar Abdul Ghaffar, Suhaila Abdul Hamid, Zargar Abubakar Garba, Jamila Abu-Rmeileh, Niveen M Acosta-Cazares, Benjamin Adams, Robert J Aekplakorn, Wichai Afsana, Kaosar Agdeppa, Imelda A Aguilar-Salinas, Carlos A Agyemang, Charles Ahmad, Mohamad Hasnan Ahmad, Noor Ani Ahmadi, Naser Ahmadvand, Alireza Ahrens, Wolfgang Ajlouni, Kamel AlBuhairan, Fadia AlDhukair, Shahla Al-Hazzaa, Hazzaa M Ali, Mohamed M Ali, Osman Alkerwi, Ala'a Al-Othman, Amani Rashed Al-Raddadi, Rajaa Alvarez-Pedrerol, Mar Aly, Eman Amarapurkar, Deepak N Amouyel, Philippe Amuzu, Antoinette Andersen, Lars Bo Anderssen, Sigmund A Angquist, Lars H Anjana, Ranjit Mohan Ansari-Moghaddam, Alireza Aounallah-Skhiri, Hajer Araujo, Joana Ariansen, Inger Aris, Tahir Arku, Raphael E Arlappa, Nimmathota Aryal, Krishna K Aspelund, Thor Assah, Felix K Assuncao, Maria Cecilia F Aung, May Soe Auvinen, Juha Avdicova, Maria Azevedo, Ana Azizi, Fereidoun Azmin, Mehrdad Babu, Bontha V Baharudin, Azli Bahijri, Suhad Baker, Jennifer L Balakrishna, Nagalla Bamoshmoosh, Mohamed Banach, Maciej Bandosz, Piotr Banegas, Jose R Barbagallo, Carlo M Barcelo, Alberto Barkat, Amina Barros, Aluisio J D Barros, Mauro V G Bata, Iqbal Batieha, Anwar M Batista, Rosangela L Battakova, Zhamilya Batyrbek, Assembekov Baur, Louise A Beaglehole, Robert Bel-Serrat, Silvia Ben Romdhane, Habiba Benedics, Judith Benet, Mikhail Berkinbayev, Salim Bernabe-Ortiz, Antonio Bernotiene, Gailute Bettiol, Heloisa Bhagyalaxmi, Aroor Bharadwaj, Sumit Bhargava, Santosh K Bi, Hongsheng Bi, Yufang Biehl, Anna Bika Lele, Elysee Claude Bikbov, Mukharram Bista, Bihungum Bjelica, Dusko J Bjerregaard, Peter Bjertness, Espen Bjertness, Marius B Bjorkelund, Cecilia Blokstra, Anneke Bo, Simona Bobak, Martin Boddy, Lynne M Boehm, Bernhard O Boeing, Heiner Boggia, Jose G Boissonnet, Carlos P Bonaccio, Marialaura Bongard, Vanina Bopp, Matthias Borchini, Rossana Borghs, Herman Braeckevelt, Lien Braeckman, Lutgart Bragt, Marjolijn C E Brajkovich, Imperia Branca, Francesco Breckenkamp, Juergen Breda, Joao Brenner, Hermann Brewster, Lizzy M Brian, Garry R Brinduse, Lacramioara Bruno, Graziella Bueno-de-Mesquita, H Bas Bugge, Anna Buoncristiano, Marta Burazeri, Genc Burns, Con Cabrera de Leon, Antonio Cacciottolo, Joseph Cai, Hui Cama, Tilema Cameron, Christine Camolas, Jose Can, Gamze Can, Gunay Candido, Ana Paula C Canete, Felicia Capanzana, Mario V Capuano, Eduardo Capuano, Vincenzo Cardoso, Viviane C Carlsson, Axel C Carmuega, Esteban Carvalho, Maria J Casanueva, Felipe F Casas, Juan-Pablo Caserta, Carmelo A Celikcan, Ertugrul Censi, Laura Cesar, Juraci A Chamukuttan, Snehalatha Chan, Angelique W Chan, Queenie Chaturvedi, Himanshu K Chaturvedi, Nishi Che Abdul Rahim, Norsyamlina Chen, Chien-Jen Chen, Fangfang Chen, Huashuai Chen, Shuohua Chen, Zhengming Cheng, Ching-Yu Cheng, Yiling J Chetrit, Angela Chikova-Iscener, Ekaterina Chiolero, Arnaud Chiou, Shu-Ti Chirlaque, Maria-Dolores Cho, Belong Cho, Yumi Christensen, Kaare Christofaro, Diego G Chudek, Jerzy Cifkova, Renata Cilia, Michelle Cinteza, Eliza Claessens, Frank Clarke, Janine Clays, Els Concin, Hans Confortin, Susana C Cooper, Cyrus Coppinger, Tara C Costanzo, Simona Cottel, Dominique Cowell, Chris Craig, Cora L Crampin, Amelia C Crujeiras, Ana B Cruz, Juan J Cucu, Alexandra Cui, Liufu Dallongeville, Jean Damasceno, Albertino Damsgaard, Camilla T Dankner, Rachel Dantoft, Thomas M D'Arrigo, Graziella Dasgupta, Parasmani Dastgiri, Saeed Dauchet, Luc Davletov, Kairat De Backer, Guy De Bacquer, Dirk De Curtis, Amalia de Gaetano, Giovanni De Henauw, Stefaan de Oliveira, Paula Duarte De Ridder, Karin de Rooij, Susanne R De Smedt, Delphine Deepa, Mohan Deev, Alexander D Dehghan, Abbas Delisle, Helene Delpeuch, Francis Dennison, Elaine Deschamps, Valerie Dhana, Klodian Dhimal, Meghnath Di Castelnuovo, Augusto F Dias-da-Costa, Juvenal Soares Diaz, Alejandro Dika, Zivka Djalalinia, Shirin Do, Ha T P Dobson, Annette J Donati, Maria Benedetta Donfrancesco, Chiara Donoso, Silvana P Doring, Angela Dorobantu, Maria Dorosty, Ahmad Reza d'Orsi, Eleonora Doua, Kouamelan Drygas, Wojciech Duan, Jia Li Duante, Charmaine A Duda, Rosemary B Duleva, Vesselka Dulskiene, Virginija Dumith, Samuel C Dzerve, Vilnis Dziankowska-Zaborszczyk, Elzbieta Eddie, Ricky Egbagbe, Eruke E Eggertsen, Robert Eiben, Gabriele Ekelund, Ulf El Ati, Jalila Eldemire-Shearer, Denise Eliasen, Marie Elliott, Paul Engle-Stone, Reina Erasmus, Rajiv T Erem, Cihangir Eriksen, Louise Eriksson, Johan G Escobedo-de la Pena, Jorge Evans, Alun Ezzati, Majid Faeh, David Fall, Caroline H Farrugia Sant'Angelo, Victoria Farzadfar, Farshad Fattahi, Mohammad R Felix-Redondo, Francisco J Ferguson, Trevor S Fernandes, Romulo A Fernandez-Berges, Daniel Ferrante, Daniel Ferrari, Marika Ferreccio, Catterina Ferrer, Eldridge Ferrieres, Jean Fijalkowska, Anna Fink, Gunther Fischer, Krista Flores, Eric Monterubio Foger, Bernhard Foo, Leng Huat Forslund, Ann-Sofie Forsner, Maria Fouad, Heba M Francis, Damian K Franco, Maria do Carmo Franco, Oscar H Frontera, Guillermo Fuchs, Flavio D Fuchs, Sandra C Fujita, Yuki Furusawa, Takuro Gaciong, Zbigniew Gafencu, Mihai Galeone, Daniela Galvano, Fabio Gao, Jingli Garcia-de-la-Hera, Manoli Gareta, Dickman Garnett, Sarah P Gaspoz, Jean-Michel Gasull, Magda Gates, Louise Gazzinelli, Andrea Geiger, Harald Geleijnse, Johanna M Ghanbari, Ali Ghasemi, Erfan Ghasemian, Anoosheh Gheorghe-Fronea, Oana-Florentina Giampaoli, Simona Gianfagna, Francesco Gill, Tiffany K Giovannelli, Jonathan Gironella, Glen Giwercman, Aleksander Godos, Justyna Gogen, Sibel Goldsmith, Rebecca A Goltzman, David Goncalves, Helen Gonzalez, Angel R Gonzalez-Chica, David A Gonzalez-Gross, Marcela Gonzalez-Leon, Margot Gonzalez-Rivas, Juan P Gonzalez-Villalpando, Maria-Elena Gottrand, Frederic Graca, Antonio Pedro Graff-Iversen, Sidsel Grafnetter, Dusan Grajda, Aneta Grammatikopoulou, Maria G Gregor, Ronald D Grodzicki, Tomasz Grontved, Anders Grosso, Giuseppe Gruden, Gabriella Gu, Dongfeng Gualdi-Russo, Emanuela Gudmundsson, Elias F Gudnason, Vilmundur Guerrero, Ramiro Guessous, Idris Guimaraes, Andre L Gulliford, Martin C Gunnlaugsdottir, Johanna Gunter, Marc Guo, Xiuhua Guo, Yin Gupta, Prakash C Gupta, Rajeev Gureje, Oye Gurzkowska, Beata Gutierrez, Laura Gutzwiller, Felix Hadaegh, Farzad Hadjigeorgiou, Charalambos A Haghshenas, Rosa Halkjaer, Jytte Hardy, Rebecca Hari Kumar, Rachakulla Hassapidou, Maria Hata, Jun Haugsgjerd, Teresa He, Jiang He, Yuna Heidinger-Felso, Regina Heinen, Mirjam Hejgaard, Tatjana Hendriks, Marleen Elisabeth Henriques, Ana Hernandez Cadena, Leticia Herrala, Sauli Herrera, Victor M Herter-Aeberli, Isabelle Heshmat, Ramin Hill, Allan G Ho, Sai Yin Ho, Suzanne C Hobbs, Michael Hofman, Albert Hopman, Wilma M Horimoto, Andrea R V R Hormiga, Claudia M Horta, Bernardo L Houti, Leila Howitt, Christina Htay, Thein Thein Htet, Aung Soe Htike, Maung Maung Than Hu, Yonghua Huerta, Jose Maria Huhtaniemi, Ilpo Tapani Huidumac Petrescu, Constanta Huisman, Martijn Husseini, Abdullatif Huu, Chinh Nguyen Huybrechts, Inge Hwalla, Nahla Hyska, Jolanda Iacoviello, Licia Ibarluzea, Jesus M Ibrahim Wong, Norazizah Ibrahim, Mohsen M Ikram, M Arfan Irazola, Vilma E Ishida, Takafumi Islam, Muhammad Ismail, Aziz Al-Safi Ivkovic, Vanja Iwasaki, Masanori Jaaskelainen, Tuija Jackson, Rod T Jacobs, Jeremy M Jaddou, Hashem Jafar, Tazeen James, Kenneth Jamil, Kazi M Jamrozik, Konrad Janszky, Imre Janus, Edward Jarani, Juel Jarvelin, Marjo-Riitta Jasienska, Grazyna Jelakovic, Ana Jelakovic, Bojan Jennings, Garry Jeong, Seung-Lyeal Jiang, Chao Qiang Jimenez, Ramon O Joffres, Michel Johansson, Mattias Jokelainen, Jari J Jonas, Jost B Jorgensen, Torben Joshi, Pradeep Jovic, Dragana P Jozwiak, Jacek Juolevi, Anne Jurak, Gregor Juresa, Vesna Kaaks, Rudolf Kafatos, Anthony Kajantie, Eero O Kalter-Leibovici, Ofra Kamaruddin, Nor Azmi Kameli, Yves Kapantais, Efthymios Karki, Khem B Kasaeian, Amir Katibeh, Marzieh Katz, Joanne Katzmarzyk, Peter T Kauhanen, Jussi Kaur, Prabhdeep Kavousi, Maryam Kazakbaeva, Gyulli Keil, Ulrich Keinan-Boker, Lital Keinanen-Kiukaanniemi, Sirkka Kelishadi, Roya Kelleher, Cecily Kemper, Han C G Kerimkulova, Alina Kersting, Mathilde Key, Timothy Khader, Yousef Saleh Khalili, Davood Khateeb, Mohammad Khaw, Kay-Tee Kheiri, Bahareh Khosravi, Alireza Khouw, Ilse M S L Kiechl, Stefan Kiechl-Kohlendorfer, Ursula Killewo, Japhet Kim, Jeongseon Kim, Yeon-Yong Klimont, Jeannette Klumbiene, Jurate Knoflach, Michael Koirala, Bhawesh Kolle, Elin Kolsteren, Patrick Konig, Jurgen Korpelainen, Raija Korrovits, Paul Korzycka, Magdalena Koskinen, Seppo Kouda, Katsuyasu Kovacs, Viktoria A Kowlessur, Sudhir Koziel, Slawomir Kratzer, Wolfgang Kriemler, Susi Kristensen, Peter Lund Krokstad, Steinar Kromhout, Daan Kruger, Herculina S Kubinova, Ruzena Kuciene, Renata Kuh, Diana Kujala, Urho M Kujundzic, Enisa Kulaga, Zbigniew Kumar, R Krishna Kunesova, Marie Kurjata, Pawel Kusuma, Yadlapalli S Kuulasmaa, Kari Kyobutungi, Catherine La, Quang Ngoc Laamiri, Fatima Zahra Laatikainen, Tiina Lachat, Carl Laid, Youcef Lam, Tai Hing Lang Morovic, Maja Lanska, Vera Lappas, Georg Larijani, Bagher Latt, Tint Swe Laugsand, Lars E Lauria, Laura Lazo-Porras, Maria Le Nguyen Bao, Khanh Le Port, Agnes Le, Tuyen D Lee, Jeannette Lee, Jeonghee Lee, Paul H Lehtimaki, Terho Lemogoum, Daniel Levitt, Naomi S Lilly, Christa L Lim, Wei-Yen Lima-Costa, M Fernanda Lin, Hsien-Ho Lin, Xu Lind, Lars Linneberg, Allan Lissner, Lauren Litwin, Mieczyslaw Liu, Jing Loit, Helle-Mai Lopes, Luis Lopez, Tania Lopez-Garcia, Esther Lorbeer, Roberto Lotufo, Paulo A Lozano, Jose Eugenio Luksiene, Dalia Lundqvist, Annamari Lundqvist, Robert Lunet, Nuno Lytsy, Per Ma, Guansheng Ma, Jun Machado-Coelho, George L L Machado-Rodrigues, Aristides M Machi, Suka Maggi, Stefania Magliano, Dianna J Magriplis, Emmanuella Maire, Bernard Majer, Marjeta Makdisse, Marcia Malekzadeh, Fatemeh Malekzadeh, Reza Malhotra, Rahul Malyutina, Sofia Maniego, Lynell V Manios, Yannis Mann, Jim I Manzato, Enzo Margozzini, Paula Markaki, Anastasia Markey, Oonagh Markidou Ioannidou, Eliza Marques, Larissa Pruner Marques-Vidal, Pedro Marrugat, Jaume Martin, Rosemarie Martin-Prevel, Yves Martorell, Reynaldo Martos, Eva Marventano, Stefano Masoodi, Shariq R Mathiesen, Ellisiv B Mathur, Prashant Matijasevich, Alicia Matsha, Tandi E Mazur, Artur Mbanya, Jean Claude N McFarlane, Shelly R McKee, Martin McLachlan, Stela McLean, Rachael M McLean, Scott B McNulty, Breige A Md Yusof, Safiah Mediene-Benchekor, Sounnia Medzioniene, Jurate Mehdipour, Parinaz Meirhaeghe, Aline Meisfjord, Jorgen Meisinger, Christa Menezes, Ana Maria B Menon, Geetha R Mensink, Gert B M Mereke, Alibek Meshram, Indrapal I Metspalu, Andres Meyer, Haakon E Mi, Jie Michaelsen, Kim F Michels, Nathalie Mikkel, Kairit Milanovic, Sanja Music Miller, Jody C Minderico, Claudia S Miquel, Juan Francisco Mirkopoulou, Daphne Mirrakhimov, Erkin Misigoj-Durakovic, Marjeta Mistretta, Antonio Mocanu, Veronica Modesti, Pietro A Moghaddam, Sahar Saeeidi Mohajer, Bahram Mohamed, Mostafa K Mohammad, Kazem Mohammadifard, Noushin Mohan, Viswanathan Mohanna, Salim Mohd Yusoff, Muhammad Fadhli Mohebi, Farnam Moitry, Marie Molbo, Drude Mollehave, Line T Moller, Niels C Molnar, Denes Momenan, Amirabbas Mondo, Charles K Monterrubio, Eric A Monyeki, Kotsedi Daniel K Moon, Jin Soo Moreira, Leila B Morejon, Alain Moreno, Luis A Morgan, Karen Morin, Suzanne Mortensen, Erik Lykke Moschonis, George Mossakowska, Malgorzata Mota, Jorge Mota-Pinto, Anabela Motlagh, Mohammad Esmaeel Motta, Jorge Msyamboza, Kelias P Mu, Thet Thet Muc, Magdalena Mugosa, Boban Muiesan, Maria Lorenza Mukhtorova, Parvina Muller-Nurasyid, Martina Murphy, Neil Mursu, Jaakko Murtagh, Elaine M Musil, Vera Nabipour, Iraj Naderimagham, Shohreh Nagel, Gabriele Naidu, Balkish M Nakamura, Harunobu Namesna, Jana Nang, Ei Ei K Nangia, Vinay B Nankap, Martin Narake, Sameer Nardone, Paola Nauck, Matthias Navarrete-Munoz, Eva Maria Neal, William A Nelis, Keiu Nelis, Liis Nenko, Ilona Nervi, Flavio Nguyen, Chung T Nguyen, Nguyen D Nguyen, Quang Ngoc Nieto-Martinez, Ramfis E Ning, Guang Ninomiya, Toshiharu Nishtar, Sania Noale, Marianna Noboa, Oscar A Norat, Teresa Norie, Sawada Noto, Davide Nsour, Mohannad Al Nurk, Eha Nyirenda, Moffat Obreja, Galina Ochoa-Aviles, Angelica M Oda, Eiji Oh, Kyungwon Ohara, Kumiko Ohtsuka, Ryutaro Olafsson, Orn Olinto, Maria Teresa Anselmo Oliveira, Isabel O Oltarzewski, Maciej Omar, Mohd Azahadi Onat, Altan O'Neill, Terence W Ong, Sok King Ono, Lariane M Ordunez, Pedro O'Reilly, Dermot Ornelas, Rui Ortiz, Ana P Ortiz, Pedro J Osler, Merete Osmond, Clive Ostojic, Sergej M Ostovar, Afshin Otero, Johanna A Overvad, Kim Owusu-Dabo, Ellis Paccaud, Fred Michel Padez, Cristina Pagkalos, Ioannis Pahomova, Elena Pajak, Andrzej Palli, Domenico Palloni, Alberto Palmieri, Luigi Pan, Wen-Harn Panda-Jonas, Songhomitra Pandey, Arvind Panza, Francesco Papandreou, Dimitrios Park, Soon-Woo Parnell, Winsome R Parsaeian, Mahboubeh Pascanu, Ionela M Patel, Nikhil D Pecin, Ivan Pednekar, Mangesh S Peer, Nasheeta Peixoto, Sergio Viana Peltonen, Markku Pereira, Alexandre C Perez, Cynthia M Perez-Farinos, Napoleon Peters, Annette Petersmann, Astrid Petkeviciene, Janina Petrauskiene, Ausra Peykari, Niloofar Pham, Son Thai Pierannunzio, Daniela Pigeot, Iris Pikhart, Hynek Pilav, Aida Pilotto, Lorenza Pistelli, Francesco Pitakaka, Freda Piwonska, Aleksandra Plans-Rubio, Pedro Poh, Bee Koon Pohlabeln, Hermann Pop, Raluca M Popovic, Stevo R Porta, Miquel Portegies, Marileen L P Posch, Georg Poulimeneas, Dimitrios Pouraram, Hamed Pourshams, Akram Poustchi, Hossein Pradeepa, Rajendra Price, Alison J Price, Jacqueline F Puder, Jardena J Pudule, Iveta Puhakka, Soile E Puiu, Maria Punab, Margus Qasrawi, Radwan F Qorbani, Mostafa Quoc Bao, Tran Radhika, Madhari S Radic, Ivana Radisauskas, Ricardas Rahman, Mahfuzar Rahman, Mahmudur Raitakari, Olli Raj, Manu Rajkumar, Hemalatha Rakhmatulloev, Sherali Ramachandra Rao, Sudha Ramachandran, Ambady Ramke, Jacqueline Ramos, Elisabete Ramos, Rafel Rampal, Lekhraj Rampal, Sanjay Rao, Kodavanti Mallikharjuna Rascon-Pacheco, Ramon A Rasmussen, Mette Redon, Josep Reganit, Paul Ferdinand M Regecova, Valeria Revilla, Luis Ribas-Barba, Lourdes Ribeiro, Robespierre Riboli, Elio Rigo, Fernando Rinaldo, Natascia Rinke de Wit, Tobias F Rito, Ana Ritti-Dias, Raphael M Rivera, Juan A Robitaille, Cynthia Rodrigues, Daniela Rodriguez-Artalejo, Fernando Rodriguez-Perez, Maria Del Cristo Rodriguez-Villamizar, Laura A Rojas-Martinez, Rosalba Rojroongwasinkul, Nipa Romaguera, Dora Rosengren, Annika Rouse, Ian Roy, Joel G R Rubinstein, Adolfo Ruhli, Frank J Ruidavets, Jean-Bernard Ruiz Moreno, Emma Ruiz-Betancourt, Blanca Sandra Russo, Paola Rust, Petra Rutkowski, Marcin Sabanayagam, Charumathi Sachdev, Harshpal S Safiri, Saeid Saidi, Olfa Salanave, Benoit Salazar-Martinez, Eduardo Salmeron, Diego Salomaa, Veikko Salonen, Jukka T Salvetti, Massimo Sanchez-Abanto, Jose Sandjaja Sans, Susana Santa-Marina, Loreto Santos, Diana A Santos, Ina S Santos, Osvaldo Santos, Rute Sanz, Sara Santos Saramies, Jouko L Sardinha, Luis B Sarrafzadegan, Nizal Saum, Kai-Uwe Savva, Savvas Savy, Mathilde Scazufca, Marcia Schaffrath Rosario, Angelika Schargrodsky, Herman Schienkiewitz, Anja Schindler, Karin Schipf, Sabine Schmidt, Carsten O Schmidt, Ida Maria Schottker, Ben Schultsz, Constance Schutte, Aletta E Sebert, Sylvain Sein, Aye Aye Selamat, Rusidah Sember, Vedrana Sen, Abhijit Senbanjo, Idowu O Sepanlou, Sadaf G Sequera, Victor Serra-Majem, Luis Servais, Jennifer Shalnova, Svetlana A Sharma, Sanjib K Shaw, Jonathan E Shengelia, Lela Shibuya, Kenji Shimizu-Furusawa, Hana Shin, Dong Wook Shin, Youchan Siani, Alfonso Siantar, Rosalynn Sibai, Abla M Silva, Antonio M Silva, Diego Augusto Santos Simon, Mary Simons, Judith Simons, Leon A Si-Ramlee, Khairil Sjoberg, Agneta Sjostrom, Michael Slowikowska-Hilczer, Jolanta Slusarczyk, Przemyslaw Smeeth, Liam Snijder, Marieke B So, Hung-Kwan Sobngwi, Eugene Soderberg, Stefan Soekatri, Moesijanti Y E Soemantri, Agustinus Solfrizzi, Vincenzo Sonestedt, Emily Song, Yi Sorensen, Thorkild I A Sossa Jerome, Charles Soumare, Aicha Spinelli, Angela Spiroski, Igor Staessen, Jan A Stamm, Hanspeter Stathopoulou, Maria G Staub, Kaspar Stavreski, Bill Steene-Johannessen, Jostein Stehle, Peter Stein, Aryeh D Stergiou, George S Stessman, Jochanan Stockl, Doris Stocks, Tanja Stokwiszewski, Jakub Stratton, Gareth Stronks, Karien Strufaldi, Maria Wany Sturua, Lela Suarez-Medina, Ramon Sun, Chien-An Sundstrom, Johan Sung, Yn-Tz Sunyer, Jordi Suriyawongpaisal, Paibul Swinburn, Boyd A Sy, Rody G Sylva, Rene Charles Szponar, Lucjan Tai, E Shyong Tammesoo, Mari-Liis Tamosiunas, Abdonas Tan, Eng Joo Tang, Xun Tanser, Frank Tao, Yong Tarawneh, Mohammed Rasoul Tarp, Jakob Tarqui-Mamani, Carolina B Taxova Braunerova, Radka Taylor, Anne Tchibindat, Felicite Tebar, William R Tell, Grethe Tello, Tania Theobald, Holger Theodoridis, Xenophon Thijs, Lutgarde Thuesen, Betina H Ticha, Lubica Timmermans, Erik J Tjonneland, Anne Tolonen, Hanna K Tolstrup, Janne S Topbas, Murat Topor-Madry, Roman Tormo, Maria Jose Tornaritis, Michael J Torrent, Maties Toselli, Stefania Traissac, Pierre Trichopoulos, Dimitrios Trichopoulou, Antonia Trinh, Oanh T H Trivedi, Atul Tsao, Yu-Hsiang Tshepo, Lechaba Tsigga, Maria Tsugane, Shoichiro Tulloch-Reid, Marshall K Tullu, Fikru Tuomainen, Tomi-Pekka Tuomilehto, Jaakko Turley, Maria L Tynelius, Per Tzotzas, Themistoklis Tzourio, Christophe Ueda, Peter Ugel, Eunice E Ukoli, Flora A M Ulmer, Hanno Unal, Belgin Uusitalo, Hannu M T Vaitkeviciute, Justina Valdivia, Gonzalo Vale, Susana Valvi, Damaskini van der Schouw, Yvonne T Van Herck, Koen Van Minh, Hoang van Rossem, Lenie Van Schoor, Natasja M van Valkengoed, Irene G M Vanderschueren, Dirk Vanuzzo, Diego Varela-Moreiras, Gregorio Varona-Perez, Patricia Vatten, Lars Vega, Tomas Veidebaum, Toomas Velasquez-Melendez, Gustavo Velika, Biruta Veronesi, Giovanni Verschuren, W M Monique Victora, Cesar G Viegi, Giovanni Viet, Lucie Vineis, Paolo Vioque, Jesus Virtanen, Jyrki K Visser, Marjolein Visvikis-Siest, Sophie Viswanathan, Bharathi Vlasoff, Tiina Vollenweider, Peter Volzke, Henry Voutilainen, Ari Voutilainen, Sari Vrijheid, Martine Vrijkotte, Tanja G M Wade, Alisha N Wagner, Aline Waldhor, Thomas Walton, Janette Wan Bebakar, Wan Mohamad Wan Mohamud, Wan Nazaimoon Wanderley, Rildo S Jr Wang, Ming-Dong Wang, Qian Wang, Xiangjun Wang, Ya Xing Wang, Ying-Wei Wannamethee, S Goya Wareham, Nicholas Weber, Adelheid Weerasekera, Deepa Weghuber, Daniel Wei, Wenbin Whincup, Peter H Widhalm, Kurt Widyahening, Indah S Wiecek, Andrzej Wijga, Alet H Wilks, Rainford J Willeit, Johann Willeit, Peter Wilsgaard, Tom Wojtyniak, Bogdan Wong, Jyh Eiin Wong, Tien Yin Wong-McClure, Roy A Woo, Jean Woodward, Mark Wu, Frederick C Wu, Jianfeng Wu, Shouling Xu, Haiquan Xu, Liang Yamborisut, Uruwan Yan, Weili Yang, Ling Yang, Xiaoguang Yang, Yang Yardim, Nazan Yaseri, Mehdi Ye, Xingwang Yiallouros, Panayiotis K Yngve, Agneta Yoosefi, Moein Yoshihara, Akihiro You, Qi Sheng You, San-Lin Younger-Coleman, Novie O Yusoff, Ahmad Faudzi Zaccagni, Luciana Zafiropulos, Vassilis Zamani, Farhad Zambon, Sabina Zampelas, Antonis Zamrazilova, Hana Zapata, Maria Elisa Zaw, Ko Ko Zdrojewski, Tomasz Zeljkovic Vrkic, Tajana Zeng, Yi Zhao, Dong Zhao, Wenhua Zheng, Wei Zheng, Yingfeng Zholdin, Bekbolat Zhou, Maigeng Zhu, Dan Zhussupov, Baurzhan Zimmermann, Esther Zuniga Cisneros, Julio